The vulnerable context of tourism development: evidence from Sri Lanka - M. S., Mohamed Aslam; Awang, Khairil Wahidin; Samdin, Zaiton; Othman, Nor'ain (Inderscience Publishers, 2014)
A large number of countries adapted tourism as a significant tool for development, but over utilisation of resources and negative impacts were claimed planned tourism development to ensure the sustainability. Sri Lanka also embarked on the tourism industry, beginning in the 1960s with planned tourism development. This paper intends to identify and understand the broader context of tourism development and its vulnerability with reference to Sri Lanka. This study adopted an inductive descriptive analysis methodology through informal and formal interviews and participant observation, in addition to a wide documentary analysis. Many researchers and authors verify that planned tourism development determines positive outcomes and attainment of desired objectives. Until 1982, Sri Lanka had recorded highly favourable growth in tourism. Since 1983 planning deficiencies, internal crises and natural disasters have curtailed the progress of planned tourism development. Conceptually, the tourism planning process provides positive outlooks of a potential tourism industry but in a broader context, political, socio-cultural, environmental and economic stability determine tourism development in a destination.